Cooking small and large portions of “biodiversity‐soup”: Miniaturized DNA metabarcoding PCRs perform as good as large‐volume PCRs - Dominik Buchner; Arne J. Beermann; Florian Leese; Martina Weiss (Ecology and Evolution, 2021)
Abstract DNA metabarcoding is a powerful tool to assess arthropod diversity in environmental bulk samples such as Malaise trap, pitfall trap, or hand net samples. While comparative performance tests for different extraction protocols, primers, and Taq polymerases have been made, the effect of different PCR volumes on bulk sample metabarcoding performance is less explored. Although using small PCR volumes reduces overall costs, they may lead to decreased taxon recovery or higher replicate variability due to increased pipetting imprecision, PCR stochasticity (PCR drift), or inhibition when using high amounts of template community DNA. We here performed a simple DNA metabarcoding experiment to test if species detection and the consistency of technical replicates decrease with decreasing PCR volume in standard reaction tubes. We used a mock community sample consisting of different amounts of DNA from 35 arthropod species, and a Malaise trap sample composed of many thousand insect specimens. PCR volumes tested were 5, 10, 15, 20, 25, and 50 µl. Both samples were replicated 14 times in the first PCR step with two technical replicates each in the second PCR step. Our data show that small PCR volumes did neither have systematically lower species detection or richness values, nor lower consistency between PCR replicates. We therefore recommend low volumes primarily depending on handling constraints. Further, we emphasize the importance of sequencing depth for taxon recovery.